Study and Analysis of SBD Detector Sensitivity Based on Au-InP and Au-GaAs Structures - K.В Reguieg; Z.В Souar; R.В Becharef (Журнал нано- та електронної фізики)
In this paper, a novel approach of materials combination is proposed to enhance the performance of Schottky Barrier Diodes (SBD) detector. High purity of gold (90В %) in combination with two different semiconductors (Indium Phosphide (InP) and Gallium Arsenide (GaAs)) are used to perform SBD samples. The current saturation and ideality factor were extracted from experimental current-voltage characterization, the results insure interesting values. Our sampleвЂ™s conductivity has been studied and confirm asymmetric in its shape. The analysis of maximum level of current sensitivity for both samples prove their peak value in the nonlinear range of SBD, thus Au-InP gives maximum sensitivity equal to 27.96В A/W and Au-GaAs has a maximum sensitivity equal to 49.33 A/W, which makes them successfully useful for detection in comparison to other works in this domain.